Modern Mandapa of the Suswani Mata Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the modern mandapa (pillared hall) of the Suswani Mata Temple. To its south side are some historical fragments consisting of Hero stones, which are worshipped as veeron ke pathar (stones of heroic people). The original location of these fragments is unknown, but today they are an integral part of the rituals performed by devotees visiting the temple.